STUDENTS' HISTORICAL THINKING ABILITY THROUGH PICTURE MEDIA IN CLASS X SOCIAL SCIENCES MAN INSAN CENDEKIA PALU CITY - Hasan Hasan; Nurhayati Nurhayati; Nuraedah Nuraedah (Jurnal Dikdas, 2021)
This study aims to analyze the implementation of the use of image media in improving students' historical thinking skills in history subjects at MAN Insan Cendekia Palu City. This research article is a qualitative research followed by using the Class Action (TK) method. The results showed that the teacher in question did not use the media in a series of learning activities that should use learning media. Data collection techniques used are observation, interviews and documentation. The subjects in this study were students of class X IPS Al Buruj MAN Insan Cendikia Palu, totaling 23 people, consisting of 15 male students and 7 female students. Qualitative data analysis uses data reduction techniques, data presentation and conclusion drawing, while quantitative analysis uses individual absorption formulas and classical completeness. The results showed that the use of image media can improve students' critical thinking skills in history subjects. This is evidenced from the test results, where 96% of students completed or as many as 22 of 23 students and 4% or as many as 1 student who did not complete during the learning process using picture media.